Voicing Rivers through ontopoetics: A co‐operative inquiry. (19th May 2021) - Kurio, Jacqueline; Reason, Peter
Abstract: A co‐operative inquiry was established to explore the experience of a panpsychic world of sentient beings rather than inert objects, a world in which mind—sentience, subjectivity, and the will of self‐realization—is a fundamental aspect of matter, just as matter is a fundamental aspect of mind. The nature of worldviews, the fundamental basis of our perceiving, thinking, valuing, and acting, is addressed and a brief outline of living cosmos panpsychism offered. The inquiry asks, could we humans, through intentional engagement, relate to the rivers as beings, subjects, or other‐than‐human persons in their own right? How might we engage with the rivers through personal relationship, ceremony, and invocation? What are the possibilities for reciprocal communication? In short, how might rivers speak?